142k views
2 votes
PLZZZ HELP!!! THIS IS TIMED!!! When solving the equation, which is the best first step to begin to simplify the equation? -2(x+3)=-10(-2)

A(-2)(-2)(x+3=-10(-2)
B-1/2(-2)(x+3)=-10(-1/2)
C-2/2(x+3)=-10(-1/2)
D-2/-10(x+3)=-10/-10

User Mattinbits
by
4.9k points

1 Answer

3 votes

Let's solve your equation step-by-step.

−2(x+3)=(−10)(−2)

Step 1: Simplify both sides of the equation.

−2(x+3)=(−10)(−2)

(−2)(x)+(−2)(3)=(−10)(−2)(Distribute)

−2x+−6=20

−2x−6=20

Step 2: Add 6 to both sides.

−2x−6+6=20+6

−2x=26

Step 3: Divide both sides by -2.

−2x

−2

=

26

−2

x=−13

User Kioko Kiaza
by
6.0k points